Why does the establishment of the starch preferring Entodinium caudatum in the rumen decrease the numbers of the fibrolytic ciliate Eudiplodinium maggii? - Bełzecki, G; Miltko, R; Michałowski, T (Folia microbiologica, 2004)
The effect of the establishment of Entodinium caudatum on the population of Eudiplodinium maggii was examined in the rumen of three sheep fed a hay/ground barley diet. The cell concentration of E. maggii were 15.9-38.5 and 11.7-12.4 x 10(3) cells per g of the rumen contents in the absence and presence of E. caudatum, respectively. Microscopic analysis showed that starch was the only material engulfed by eudiplodinia irrespective of the time after feeding and the presence or absence of E. caudatum. Up to 82-93% of individuals contained starch grains when E. maggii was the only ciliate species in the rumen; the proportion was 70-77% after entodinia had been established. The largest quantity of starch engulfed by E. maggii ciliates was 12.4-19.0 and 6.7-7.6 mg per 100 mg protozoal dry mass in the absence and presence of entodinia, respectively. No visible engulfment of hay was observed in vivo in spite of the fact that hay particles up to 42 microns in length were dominating in rumen fluid. Ingestion of fresh particles of hay separated from the rumen digesta was found when they were added in the proportion of 1 g per 40 mL suspension of ciliates. No preferential intake of starch was observed when E. maggii ciliates were incubated in vitro with a mixture of hay and barley starch. It is suggested that competition for starch between the two ciliate species was responsible for the drop in the numbers of E. maggii. This could result from a too low concentration of small particles of hay in the rumen fluid.
Keywords: škrob; Sheep; Rumen; zvířata; Population Dynamics; ekosystém; Starch; populační dynamika; ovce; Ecosystem; bachor; Trichostomatida; Animals